An experimental investigation on preparatory year EFL learners’ vocabulary achievement through interactive whiteboard (IWB) - Ahmad, Waqar; Zuraina, Ali (AJHSSR Journal, 2018)
Vocabulary is a vital part of foreign language learning and teaching process and it requires more consideration in terms of appropriate methodological choice in order to facilitate the learning process of foreign language learners. Interactive Whiteboard (IWB), which is now associated with the teaching and learning process in Saudi Arabia, and especially in the EFL classrooms provided motivation for conducting the experimental investigation concerning the effects of Interactive Whiteboard (IWB) on Preparatory Year EFL learners’vocabulary achievement. The study involved two intact groups from the Preparatory Year EFL learners at a Saudi university and were labelled as Treatment and Control groups respectively. The Treatment group was given intervention for seven weeks through the Interactive Whiteboard (IWB) while the control group with the traditional whiteboard. 40 items MCQs type vocabulary achievement test was conducted at the beginning as pre-test and again at the end of the study as post-test. The data achieved was analyzed using the SPSS and the results showed that there was significant difference between the Treatment and control groups in terms of better performance in the vocabulary.